The influence of the final and binding sentence dissolving a marriage by divorce on validity and effectiveness of the dispositions mortis causa in favour of (ex-)spouse made during the marriage - Paluch, Anna (Studia Iuridica Toruniensia, 2023)
The presented article contributes to the discussion on the legitimacy of introducing into the Polish law a regulation providing invalidity or ineffectiveness of dispositions mortis causa made in favour of the spouse during the marriage which has been subsequently dissolved by divorce. The analysis of this question was carried out in the context of regulations being in force in various Western European countries which refer to the real or hypothetical will of the testator. In the article a thesis was proposed according to which there are no reasons to consider dispositions made in fovour of the spouse during the marriage which subsequently ceased by divorce as ineffective or void. The will of the testator is manifested by the lack of revocation of such dispositions.